The Effect of Stress Levels on Blood Glucose Levels in Medical Laboratory Technology Final-Year Students - Nursidika, Perdina; Astari, Risti Maulani; Furqon, Ayi (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Final-year students are a group that experiences stress due to academic life, responsibilities, and demands from the academic world, such as completing theses, fieldwork, and other academic burden. In addition, the current pandemic may cause stress related to communication and daily life changes. Stress increases the release of epinephrine, catecholamine, glucagon, glucocorticoids, beta-endorphin, and growth hormone, which causes excessive cortisol production, increasing blood sugar levels. This study aimed to determine the relationship between stress levels and blood sugar levels in undergraduate students in medical laboratory technology. Method: This research method used a cross-sectional approach, with 35 samples that fit the inclusion criteria. The stress measuring tool used was the Depression Anxiety Stress Scale (DASS) questionnaire. Blood glucose examination using the Glucose Oxidase Peroxidase Aminoantypirin method. The analysis used in this study is the correlation test using the Chi-square test Result: Stress levels in students show normal stress at as much as 11% mild stress at 26% moderate stress at 46%, and severe stress at as much as 17%. The results of bivariate analysis between stress levels and blood glucose levels were p=0.012 (p<0.05). Conclusion: there is a significant relationship between stress levels and blood glucose levels in final-year students of D4 Medical Laboratory Technology at Jenderal Achmad Yani University, Cimahi. The results of this study became one of the prediabetes screening data. The need for stress management in students can be one of the factors to avoid the risk of diabetes.